Implementation Weighting Method for Selection Online Buying and Selling Platforms in the Digital Era - Rizal Furqan Ramadhan (School of Industrial and System Engineering, Telkom University, 2024)
With the development of the technology-based era, communication patterns can be carried out through application intermediaries. With an application intermediary, the communicator does not need to meet face-to-face. The influence of the development of information technology has penetrated the economic sector. A buying and selling transaction is one of the everyday activities carried out in the financial field. Application-based buying and selling transactions make it easier for market players, including sellers and buyers. Internet technology adds to the convenience and capacity of buying and selling transactions because people in different locations carry out these activities. Along with the various advantages of buying and selling platforms, it has impacted the emergence of different online buying and selling platforms with multiple features. From this presentation, it is necessary to develop research in the form of application design to determine or choose the ideal online buying and selling platform for online shopping activists, especially Generation Z. The weighting method used in this research is the Simple Additive Weighting method. The output of the online buying and selling platform with the highest value is Shopee, which is 23.73. The next platform is Tokopedia which is 23.33. So the Decision Support System using the Simple Additive Weighting method is suitable for choosing an ideal buying and selling platform.